Meningkatkan Kemampuan Dasar Kognitif Melalui Permainan “Rainbowling” Pada Anak Kelompok B-1 Tk Islam Al Falah Kecamatan Pesantren Kota Kediri - Suwarti, Suwarti (Universitas Nusantara PGRI Kediri, 2018)
Based on the observation on the development activities of the children of B-1 Islamic Al-Falah group of Pesantren Sub-district of Kediri City, found the low information about the children's sports, especially the sport of bowling, and lack of enthusiasm and enthusiasm in teaching and learning activities possibly caused by less attractive and tend to be passive for children. Accordingly, an interesting, effective, and fun learning strategy is needed to develop the child's cognitive basic skills. Through the game, Rainbowling is expected to develop the child's cognitive basic skills easily and the child does not feel bored. The form of action that will be done is through the game